2D VS2@MXene Based Zinc Ion Batteries with SPANI‐Contained Electrolyte Enables Dendrite‐Free Anode for Stable Cycling. Issue 4 (31st January 2023) - Meng, Peiyu; Wang, Wei; Shang, Jiayin; Liu, Pan; Xu, Hao; Wang, Qiguan; Wang, Sumin; Wang, Feifei; Wang, Xinhai
Abstract: Regarded as one of the popular cathode materials in aqueous zinc ion batteries (ZIBs), VS2 has unsatisfied cycling stability and relatively low capacity owing to its poor conductivity and low mechanical properties. To this regard, compositing VS2 with high‐conductive 2D transition metal carbide (MXene) has been an effective method recently. However, the Zn dendrite on the anode electrode derived from the uncontrollable sluggish migration of solvated Zn 2+ /H2 O ions seriously threatens the application safety of ZIB batteries. To effectively regulate the diffusion of zinc ions, in this work a conductive polymeric electrolyte of sulfonated polyaniline (SPANI) is added in the electrolyte solution. Under the Zn 2+ /SPANI interactions confirmed by X‐ray diffraction, Raman, and zeta potential experiments, the Zn 2+ /H2 O combination is weakened, and the deposition rate of Zn 2+ is increased evaluated by the galvanostatic intermittent titration technique. Theoretical simulation shows that the electrostatic shielding by SPANI combining Zn 2‐ at the zinc/electrolyte interface has important contribution to the significant suppression of Zn dendrite. Accordingly, the fabricated VS2 @MXene||ZnSO4 +SPANI||Zn battery shows high capacity (368.0 mAh g ‐1 at 0.1 A g ‐1 ), which remains 96% after 5000 cyclic charge–discharge operations. This work develops an available strategic idea for suppressing growth of metallic dendrites to improve the ZIB performances. Abstract : A conductive polymeric electrolyte of sulfonated polyaniline (SPANI) is added in the electrolyte of aqueous zinc ion batteries. Under the Zn 2+ /SPANI interactions, the Zn 2+ /H2 O combination is weakened, and the migration rate of Zn 2+ is positively regulated, resulting in the significant suppression of Zn dendrites. The fabricated VS2 @MXene||ZnSO4 +SPANI||Zn battery shows high capacity and excellent cycling stability.